EFEKTIFITAS SOSIALISASI SEBAGAI PENARIK MINAT NASABAH PERBANKAN SYARIAH DI MASA PEDEMI COVID-19 - Agus Miftakus Surur; Atdina Aufa (Jurnal Ilmu Komunikasi PROGRESSIO, 2020)
During the Covid-19 epidemic, the economy is currently weakening, many people have been laid off from their previous jobs. It even has an impact on society's MSMEs whose income has also decreased, because this is what people currently need for daily living or even people who are laid off will make a business that can run even in the current Covid-19 era and implement appropriate strategies with health protocols, and as a financial institution in charge of distributing funds to people in need, they must be clever in interacting with customers so that customers choose the financial institution and trust it so that they are willing to use the services of this financial institution, because socialization in the world of work is a matter which is important to know the nature and characteristics of each person. This research was conducted with the aim of providing an insight into Islamic financial institutions to attract customers in the current pandemic.